Economics of ginger (Zingiber officinale Rose.) production in Amravati District (Maharashtra, India) - BHOLE, S H GAIKWAD, P V THORVE, B D (Journal of Spices and Aromatic Crops, 1998)
The economics of production of ginger (Zingiber officinale) in Anjangaon Surji Taluka of Amravati District (Maharashtra, India) was studied during 1995-96. The study indicated that cost of cultivation and gross returns were positively related with size of the holding. The overall cost of cultivation was Rs. 1,32,415.63 per ha and Rs. 1012.04 per qtl. The overall net returns at cost C (which included all costs) was Rs. 50,399.23 per ha. However, net returns decreased with.size of holdings. The overall input-output ratio at cost C was 1.38.